The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1097/shk.0000000000000470
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lipopolysaccharide Structure in Monocyte Activation and Cytokine Secretion

Abstract: Background The lipopolysaccharide (LPS) molecule is composed of a hydrophobic lipid region (Lipid A), an oligosaccharide core, and an O-Antigen chain. Lipid A has been described as the molecular region responsible for inducing activation of immune cells. We hypothesize that the O-Antigen plays a critical role in the activation and responsiveness of mononuclear cell immune function. Methods Peripheral blood mononuclear cells (PBMCs) from healthy volunteers were stimulated with LPS, LPS with attenuated O-Antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…Previous studies implicated that LPS signal transduction lead to activation of MAP kinases and cytokine productions in monocytes . Our results showed that treatment with LPS activated all p38, JNK and ERK kinases in monocytes.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Previous studies implicated that LPS signal transduction lead to activation of MAP kinases and cytokine productions in monocytes . Our results showed that treatment with LPS activated all p38, JNK and ERK kinases in monocytes.…”
Section: Discussionsupporting
confidence: 70%
“…In particular, the level of IL-33 and the magnitude of 15,18 Previous studies implicated that LPS signal transduction lead to activation of MAP kinases and cytokine productions in monocytes. 19,20 Our results showed that treatment with LPS activated all p38, JNK and ERK kinases in monocytes. In addition, the pretreatment of IL-33 in monocytes synergically promoted the LPS-stimulated cytokine secretion through ERK1/2, but not p38 and JNK, suggesting the molecular mechanism involved in IL-33 signalling in response to the overwhelming systemic inflammation.…”
Section: Discussionmentioning
confidence: 65%
“…Monocyte stimulation by LPS-TLR4 engagement triggers distinct signaling pathways, resulting in increased expression of inflammatory and regulatory cytokines ( 33 35 ). Since PI3K activation is dependent on lipid raft recruitment ( 36 ), we initially investigated whether HP-BCD treatment would affect PI3K expression induced by LPS.…”
Section: Resultsmentioning
confidence: 99%
“…The impaired ability of HP-BCD-treated monocytes to respond to LPS resulted from transcriptional regulation of IL-10 and TNF-α. LPS-induced upregulation of TNF-α and IL-10 mRNA in PBMCs was shown to be dependent on activation of different MAP kinases ( 34 , 35 ). MAPKs were also involved in CD36-mediated cell signaling ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…RAW264.7 monocytes were incubated with 100 ng mL À1 of lipopolysaccharides (LPS, Sigma) for 48 hours to induce macrophage differentiation. 45,46 Ex vivo superoxide scavenging assay…”
Section: Cell Culturementioning
confidence: 99%